Expanding the repertoires of practice of multilingual science student teachers through a decolonial approach to academic literacies at an elite English medium university - Abdulatief, Soraya (School of Education, 2022)
The need to prepare science teachers in South Africa to respond to a heterogenous language and literacies context where multilingualism is the norm and where school conditions may shift rapidly is urgent. However, students arrive at university with varying resources and some, due to historical inequality, may not be able to meet the academic literacies demands of the university courses for which they register, and are often institutionally described as “at risk” or underprepared. Drawing on academic literacies and decoloniality theorising, this study examines the apprenticeship into the coloniality of schooling for African language speaking students locating deficit, not in the students but in the lingering colonial ideologies of language and literacy in the schooling and higher education systems. The research uses a qualitative approach and is a case study in the form of a participant intervention that addresses the academic and multiliteracies challenges faced by five African language speakers registered for a one-year Postgraduate Certificate in Education (PGCE) in science education at an elite English medium university in South Africa. I also consider whether taking a decolonial approach to academic literacies could expand the students' repertoires of practice and their production of texts in the PGCE programme. In addition, I investigate the participants' early experiences of coloniality in education; the academic and multimodal practices needed by student teachers; how African languages could be used as a resource for learning; and the role spaces outside of the university campus played in developing students' identities as science teachers and in their construction of multimodal repertoires. The theoretical framework draws on decolonial theory (Mignolo 2007; Quijano 2007; Ngugi wa ‘Thiongo 1986) and a social practices approach to academic literacies (Street 1985; Lillis 2001; New Literacy Studies 1993 and the Pedagogy of Multiliteracies; and multimodality e.g. New London Group 2000). The research findings show how African language speaking students' learning and literacies experiences from school to university continue to be shaped by coloniality, specifically the use of English as the language of instruction. Additional findings consider the specific knowledge and experiences student teachers require to successfully navigate university courses and professional practice; and what practices the demystification of academic literacies knowledge entails in a teacher education course. Taking a decolonial approach to academic literacies repositioned the students as capable and demonstrated that the problem lay not with the students, but with the system specifically under-resourced educational practices such as multimodal learning and academic literacies and continuing colonial ideologies of language and literacy.